(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2017)
In this work, graphene oxide (GO) and reduced GO (rGO) thin films were fabricated from GO and rGO using the custom-made and commercial surfactants, which were sodium 1,4-bis (neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-sulphonate and sodium dodecyl sulphate, respectively. The GO solution was synthesized using electrochemical exfoliation method followed by reduction process utilizing hydrazine hydrate to produce rGO solution. The GO and rGO transfer process were done using spraying deposition method on fluorine-doped tin oxide substrate. The fabricated GO and rGO thin films consists of several layers resulted in high transparency over 85% with maximum transmittance of 93.69%. Based on several characterizations, the fabricated GO and rGO thin films have potential to be applied as transparent conductive electrode. Key words: Custom-made, Surfactant, Electrochemical, Spraying, Electrode. Â ABSTRAK Dalam penelitian ini, film tipis grafin oksida (GO) dan grafin oksida yang direduksi (rGO) difabrikasi dari GO dan rGO menggunakan surfaktan yang dibuat khusus dan surfaktan komersial yaitu secara berurutan adalah sodium 1,4-bis (neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-sulphonate dan sodium dodecyl sulphate. Larutan GO disintesis menggunakan metode eksfoliasi elektrokimia diikuti dengan proses reduksi menggunakan hidrazin hidrat untuk menghasilkan larutan rGO. Proses transfer GO dan RGO dilakukan dengan menggunakan metode deposisi penyemprotan diatas substrat oksida timah oksida dengan doping florin. Film tipis GO dan rGO yang difabrikasi terdiri dari beberapa lapis dengan transparansi tinggi mencapai 85% dengan transmitansi maksimum sebesar 93,69%. Berdasarkan beberapa karakterisasi, film tipis GO dan rGO ini memiliki potensi untuk diaplikasikan sebagai elektroda konduktif transparan. Kata Kunci: dibuat khusus, surfaktan, elektrokimia, penyemprotan, elektroda